Man on the moon - Suen, Anastasia; Huang, Benrei (New York : Puffin Books, 2002)
Describes in illustrations and simple text the Apollo 11 mission to the moon, culminating in man's first lunar landing.
First published: Viking, 1997.
Book Links (A.L.A.)
Booklist
School Library Journal
2.8
K-3
Keywords: Apollo 11 (Spacecraft) -- Juvenile literature; Project Apollo (U.S) -- Juvenile literature; Apollo 11 (Spacecraft); Project Apollo (U.S.); Apollo 11 (Spacecraft); Space flight to the moon -- Juvenile literature; Space flight to the moon; Apollo project; Space flight to the moon